Still a contribution or rather a “healthcare” tax? Remarks against the theoretical perspective. (Discourse of Law and Administration, 2023)
Health insurance contribution as a public levy was a subject of several changes duringlast period of time under the so-called “Polski Ład” (“Polish Deal”) reforms. Still this levy for sometime now demonstrated a tendency to differ from the theoretical backgrounds of public contribution,even considering the specific of the latter. Taking into the account the health insurance contributionstructure, its aim and functions some new insights on the issue seem to be possible. Expandingcompulsory and commonality of the public health insurance, cancelling the link between the healthservices from the public health insurance and the obligation to pay the contribution or, last but notleast, using the health care contribution by the state as a mean to fund its public tasks in the fieldof health care in a broad sense (including also the non-insured or the services from beyond the insurancescope) diverges the said levy from its model even more than currently observed in the doctrine.The health care insurance contribution likely tends to shift from “the public contribution withexceptions” into a so-called specific tax – a levy from which the proceeds are used to finance certainexpenditure, in this case: public tasks in the field of the health care.
Keywords: health care contribution; tax; specific tax; Polish Deal; levy; health care financing